# RS Aggarwal Solutions Class 10 Chapter 7 Trigonometric Identities

Here you can get solutions of RS Aggarwal Solutions Class 10 Chapter 7 Trigonometric Identities. These Solutions are part of RS Aggarwal Solutions Class 10. we have given RS Aggarwal Solutions Class 10 Chapter 7 Trigonometric Identities download pdf.

## RS Aggarwal Solutions Class 10 Chapter 7 Trigonometric Identities

### RS Aggarwal Class 10 Solutions Trigonometric Identities Exercise 7A

Question 1:
Solution:

(i) (1 – cos2θ) cosec2θ = 1

L.H.S. = (1 – cos2θ) cosec2θ

= (sin2θ) × cosec2θ

(Using identity sin2θ + cos2 θ = 1)

= 1/ cosec2θ × cosec2θ

= 1

= R.H.S.

Hence Proved.

(ii) (1 + cot2θ) sin2θ = 1

L.H.S. = (1 + cot2θ) × sin2 θ

= (cosec2 θ) × sin2 θ

(Using identity 1 + cot2 θ = cosec2 θ)

= 1/ sin2θ × sin2 θ

= 1

= R.H.S.

Hence Proved.

Question 2:

Solution:

(i) (sec2θ − 1) cot2θ = 1

L.H.S. = (sec2 θ – 1) × cot2 θ

= (tan2θ) x cot2θ

(using identity 1 + tan2 θ = sec2 θ)

= 1/cot2θ x cot2θ

= 1

= R.H.S.

Hence Proved.

(ii) (sec2θ − 1) (cosec2θ − 1) = 1

L.H.S. = (sec2 θ – 1)(cosec2 θ – 1)

= (tan2θ) × cot2θ

(using identity 1 + cot2 θ = cosec2 θ and 1 + tan2 θ = sec2 θ)

= tan2θ x 1/tan2θ

= 1

= R.H.S.

Hence Proved.

(iii) (1− cos2θ) sec2θ = tan2θ

L.H.S. = (1 – cos2 θ) sec2 θ

= (sin2θ) × (1/cos2θ)

(using identity sin2 θ = 1- cos2 θ)

= tan2 θ

= R.H.S.

Hence Proved.

Question 3: Prove

Question 4: Prove
Solution:

(i)(1 + cos θ) (1 − cos θ) (1 + cot2θ) = 1

LHS: (1 + cos θ) (1 − cos θ) (1 + cot2θ)

= (1 – cos2 θ) × cosec2 θ

(Using sin2 θ + cos2 θ = 1)

= (sin2 θ) × cosec2 θ

= sin2 θ x 1/sin2 θ

= 1

= R.H.S.

Hence Proved

(ii) cosec θ (1 + cos θ) (cosec θ − cot θ) = 1

L.H.S.

cosec θ (1 + cos θ) (cosec θ − cot θ)

= (cosec θ + cosec θ cos θ)(cosec θ – cot θ)

We know, cosec θ = 1/sin θ and cot θ = cosθ/sinθ

= (cosec θ + cot θ)(cosec θ – cotθ)

Apply formula: (a + b)(a – b) = a2 – b2

= cosec2 θ – cot2 θ

= 1

= R.H.S.

Hence proved.

Question 5:
Solution:

(i)

L.H.S.

= cot2 θ – 1/sin2θ

= cos2θ/sin2θ – 1/sin2θ

= (cos2θ – 1)/sin2θ

=-sin2θ/sin2θ

= -1

= R.H.S

(ii)

L.H.S.

= tan2 θ – 1/cos2θ

= sin2θ/cos2θ – 1/cos2θ

= (sin2θ – 1)/cos2θ

=-cos2θ/cos2θ

= -1

= R.H.S

(iii)

L.H.S.

= cos2 θ + 1/(1+cot2θ

= cos2 θ + 1/cose2θ

= cos2 θ + sin2θ

= 1

= R.H.S

Question 6: Prove

Question 7:

Solution:

(i) L.H.S.

= sec θ (1 − sin θ) (sec θ + tan θ)

= cos2θ/cos2θ

= 1

= R.H.S.

(ii) L.H.S. = sin θ (1 + tan θ) + cos θ (1+ cot θ)

= sin θ (1 + sin θ/cos θ) + cos θ (1+ cos θ/sinθ)

= sin θ{(cosθ +sinθ )/cos θ} + cos θ{(sinθ+cosθ )/sinθ}

=(cos θ + sin θ) (sinθ/cos θ + cos θ/sinθ)

= (cos θ + sin θ)/cos θ sin θ

= cosec θ + sec θ

= R.H.S.

Question 8:

(ii)

= 1/cos θ

= sec θ

= R.H.S.

Question 9: Prove

Question 10: Prove

## Exercise 7B

Question 1:
Solution:

a cos θ + b sin θ = m

Squaring equation, we get

a2 cos2 θ + b2 sin2 θ + 2ab cos θ sin θ = m2 ……(1)

Again Square equation, a sin θ – b cos θ = n

a2 sin2 θ + b2 cos2 θ – 2ab cos θ sin θ = n2 ……(2)

a2 cos2 θ + b2 sin2 θ + 2ab cos θ sin θ + a2 sin2 θ + b2 cos2 θ – 2ab cos θ sin θ = m2 +n2

a2 (cos2 θ + sin2θ) + b2 (cos2 θ + sin2 θ) = m2 + n2

(Using cos2 θ + sin2θ = 1)

a2 + b2 = m2 + n2

Hence Proved.

Question 2:
Solution:

a sec θ + b tan θ = x

a tan θ + b sec θ = y

Squaring above equations:

a2 sec2 θ + b2 tan2 θ + 2ab sec θ tan θ = x2 …..(1)

a2 tan2 θ + b2 sec2 θ + 2ab sec θ tan θ = y2 ….(2)

Subtract equation (2) from (1):

a2 (sec2 θ – tan2 θ) + b2 (tan2 θ – sec2 θ) = x2 – y2

(using sec2 θ = 1 + tan2 θ)

or a2 – b2 = x2 – y2

Hence proved.

Question 3:
Solution:

x/a sin θ – y/b cos θ = 1

x/a cos θ + y/b sin θ = 1

Squaring both the equations, we have

x2/a2 sin2 θ + y2/b2 cos2 θ – 2 xy/ab cos θ sin θ = 1 ….(1)

x2/a2 cos2 θ + y2/b2 sin2 θ + 2 xy/ab cos θ sin θ = 1 ……(2)

Add (1) and (2), we get

x2/a2(sin2 θ + cos2 θ) + y2/b2 (sin2 θ + cos2 θ) = 1+1

(Using cos2 θ + sin2θ = 1)

x2/a2 + y2/b2 = 2

Question 4:
Solution:

(sec θ + tan θ) = m …(1) and

(sec θ − tan θ) = n ….(2)

Multiply (1) and (2), we have

(sec θ + tan θ) (sec θ – tan θ) = mn

(sec2 θ – tan2 θ) = mn

(Because sec2 θ – tan2 θ=1)

1 = mn

Or mn = 1

Hence Proved

Question 5:

Solution:

(cosec θ + cot θ) = m …(1) and

(cosec θ − cot θ) = n …(2)

Multiply (1) and (2)

(cosec2 θ – cot2 θ) = mn

(Because cosec2 θ – cot2 θ = 1)

1 = mn

Or mn = 1

Hence Proved

Question 6:
Solution:

x = a cos3 θ

y = b sin3 θ

L.H.S.

= cos2 θ + sin2 θ

= 1

= R.H.S.

Question 7:
Solution:

(tan θ + sin θ) = m and (tan θ − sin θ) = n

To Prove: (m2 − n2)2 = 16mn

L.H.S. = (m2 − n2)2

= [(tan θ + sin θ)2 – (tan θ − sin θ)2]2

= (4tan θ sin θ)2

= 16 tan2 θ sin2 θ …(1)

R.H.S. = 16mn

= 16(tan θ + sin θ)(tan θ − sin θ)

= 16(tan2 θ − sin2 θ)

= 16 [{sin2 θ (1-cos2 θ)/cos2θ]

= 16 x sin2 θ/cos2θ x (1-cos2 θ)

= 16 tan2 θ sin2 θ …(2)

From (1) and (2)

L.H.S. = R.H.S.

Question 8:
Solution:

(cot θ + tan θ) = m and (sec θ − cos θ) = n

m = 1/tanθ + tan θ = (1+ tan2 θ)/ tan θ = sec2 θ / tan θ

= 1/sinθcosθ

or m = 1/sinθcosθ

Again, n = sec θ − cos θ

= 1/cosθ − cos θ

= (1 – cos2 θ)/cosθ

= sin2 θ/cos θ

or n = sin2 θ/cos θ

To prove: (m2n)^(2/3) − (mn2)^(2/3) = 1

L.H.S.

(m2n)^(2/3) − (mn2)^(2/3)

Substituting the values of m and n, we have

= (1 – sin2 θ)cos2 θ

(We know, 1 – sin2 θ = cos2 θ)

= cos2 θ/ co2 θ

= 1

=R.H.S.

Hence proved.

Question 9:
Solution:

(cosec θ − sin θ) = a3 and (sec θ − cos θ) = b3

(cosec θ − sin θ) = a3

(1/sinθ − sin θ) = a3

cos2θ/sinθ = a3

And a2 = (a3)^(2/3) = (cos2θ/sinθ )^(2/3) …..(1)

Again

(sec θ − cos θ) = b3

(1/cosθ − cos θ) = b3

= sin2 θ/cosθ = b3

And, b2 = (b3)^(2/3) = (sin2 θ/cosθ)^(2/3)

To Prove:a2b2(a2 + b2) = 1

L.H.S.

a2b2(a2 + b2)

= sin2 θ + cos2 θ

= 1

=R.H.S.

Hence proved.

Question 10:
Solution:

(2 sin θ + 3 cos θ) = 2 …(1)

(2 sin θ + 3 cos θ)2 + (3 sin θ – 2 cos θ)2

= 4sin2 θ + 9 cos2 θ + 12sin θ cos θ + 9 sin2 θ + 4 cos2 θ – 12 sin θ cos θ

= 13sin2 θ + 13 cos2 θ

= 13(sin2 θ + cos2 θ)

= 13

(Because (sin2 θ + cos2 θ) = 1)

=> (2 sin θ + 3 cos θ)2 + (3 sin θ – 2 cos θ)2 = 13

Using equation (1)

=> (2)2 + (3 sin θ – 2 cos θ)2 = 13

=> (3 sin θ – 2 cos θ)2 = 9

or (3 sin θ – 2 cos θ) = ± 3

Hence Proved.

## Exercise 7C

Question 1:
Solution:

(1 – sin2θ) sec2 θ = (cos2 θ) × 1/cos2 θ

= 1

Question 2:
Solution:

(1-cos2θ)cosec2θ

= sin2θ x 1/sin2θ

= 1

Question 3:
Solution:

(1+tan2θ)cos2θ = sec2 θ x 1/sec2 θ

= 1

Question 4:
Solution:

(1+cot2θ)sin2θ = cose2θ x 1/cose2θ

= 1

Question 5:
Solution:

sin2θ + 1/(1+tan2θ)

= sin2θ + 1/(sec2θ)

= sin2θ + cos2θ

= 1

Question 6:
Solution:

(cot2θ – 1/sin2θ ) = (cos2θ/sin2θ – 1/sin2θ )

= (cos2θ – 1)/sin2θ

= -sin2θ/sin2θ

= -1

Question 7:
Solution:

sinθ cos(90°-θ)+cosθ sin(90°-θ) = sinθ x sinθ + cosθ x cosθ

= sin2θ + cos2θ

= 1

Question 8:
Solution:

cosec2(90°-θ) – tan2θ = sec2θ – tan2θ

= 1

Question 9:
Solution:

sec2θ(1+sinθ)(1-sinθ) = sec2θ(1-sin2 θ)

= sec2θ x cos2θ

= 1/cos2θ x cos2θ

= 1

Question 10:
Solution:

cosec2θ(1+cosθ)(1-cosθ) = cosec2θ (1-cos2 θ)

= cosec2θ x sin2θ

= cosec2θ x 1/cosec2θ

= 1

Question 11:
Solution:

sin2θ cos2θ(1+tan2θ)(1+cot2θ) = sin2θ x cos2θ x sec2θ x cosec2θ

= sin2θ x cos2θ x 1/cos2θ x 1/sin2θ

=1

Question 12:
Solution:

(1+tan2θ)(1+sinθ)(1-sinθ) = sec2θ(1-sin2 θ)

= sec2θ x cos2θ

= 1/cos2θ x cos2θ

= 1

Question 13:
Solution:

3cot2θ – 3cosec2θ = 3(cot2θ – cosec2θ)

= 3 x -1

= -3

Question 14:
Solution:

4tan2θ – 4/cos2θ = 4 x sin2θ/cos2θ – 4/cos2θ

= (4(sin2θ – 1))/cos2θ

= 4 (-cos2θ) / cos2θ

= -4

Question 15:
Solution:

(tan2θ – sec2θ) / (cot2θ – cose2θ) = -1/-1

= 1

(Using 1 + cot2θ = cose2θ and 1 + tan2θ = sec2θ)

Complete RS Aggarwal Solutions Class 10

If You have any query regarding this chapter, please comment on below section our team will answer you. We Tried our best to give complete solutions so you got good marks in your exam.

If these solutions have helped you, you can also share ncertsolutionsfor.com to your friends.

Best of Luck For Your Future!!